Revising Strategy Instruction in Inclusive Settings: Effects for English Learners and Novice Writers. Issue 3 (16th August 2013) - De La, Susan; Sherman, Cindy K.
<x xml:space="preserve">Abstract</x> Twenty‐three students with varying academic and linguistic profiles were taught a strategy for revising expository essays, using the Self‐Regulated Strategy Development model for instruction. Students learned basic revising tactics and to consider text structure as they managed decisions on how to improve their essays. Instructional effects were assessed using a multiple baseline with multiple probes in baseline design. Positive results were found for English learners, including those who were identified as having learning disabilities, or who were low‐, average‐ and high‐achieving writers; moreover, results were equally positive for students who were not English learners. After instruction and 4 weeks later, students revised more, produced more revisions that improved text, and revised longer text segments, which resulted in an improvement in overall quality.